Transcriptome Analysis of Newly Emerged Honeybees Exposure to Sublethal Carbendazim During Larval Stage - Wang, Kang; Fan, Rong-Li; Ji, Wen-Na; Zhang, Wen-Wen; Chen, Xiao-Mei; Wang, Shuang; Yin, Ling; Gao, Fu-Chao; Chen, Guo-Hong; Ji, Ting (Frontiers in Genetics, 2018)
There are increasing concerns regarding the impact of agrochemical pesticides on non-target organisms. Pesticides could cause honeybee abnormal development in response to neurotoxins such as neonicotinoid. However, knowledge of carbendazim, a widespread fungicide in beekeeping practice, influencing on honeybee (Apis mellifera L.) brain development is lacking. Large-scale transcriptome approaches were applied to determine the changes in global gene expression in the brains of newly emerged honeybees after carbendazim exposure during the larval stage. To further understand the effects of carbendazim on the brain development of honeybees, the functions of differentially expressed genes were compared between the treatment and control groups. We found that neuroregulatory genes were down-regulated after carbendazim exposure, which suggest the neurotoxic effects of this fungicide on honeybee nervous system. Carbendazim exposure also altered the expression of genes implicated in metabolism, transport, sensor, and hormone. Notably, larvae in the carbendazim-treated group observed longer time to shift into the dormant pupal state than the control group. Moreover, a low juvenile hormone and high ecdysone titers were found in the treatment group compared to control group. The data is the first report of neurotoxic effects on honeybee caused by carbendazim, and the sublethal carbendazim may disturb honeybee development and is a potential chemical threating the honeybee colonies.